Introduction of the circular tube in the carrying system of gondola cars to ensure the rational strength index - Фомін, Олексій Вікторович (Technology audit and production reserves, 2015)
Features and results of the study on the introduction of round pipes in the carrying systems of gondola cars based on the proposed method by the author are presented in the article. The use of such method allows minimal consumption of materials of introduced elements under the conditions of strength and operational reliability by ensuring rational indicators of strength. Results of complex theoretical and computational testing, computer modeling, durability and operational reliability of improved design of gondola cars pointed to its performance and efficiency of the implemented technical solutions. So as a result of its test of strength in all cases calculated according to calculation mode it is found that the resulting equivalent load does not exceed the allowable normalized their values of fatigue strength (at the base of test in 107 cycles) is provided, project service life is more than 32 years. In addition, the results of additional analysis to ensure strength in welded joints have also confirmed their performance.